Global Britain's strategic problem East of Suez. (11th May 2021) - James, William D.
Abstract: Why did Britain withdraw from its military bases in the Arabian Peninsula and Southeast Asia midway through the Cold War? Existing accounts tend to focus on Britain's weak economic position, as well as the domestic political incentives of retrenchment for the ruling Labour Party. This article offers an alternative explanation: the strategic rationale for retaining a permanent presence East of Suez dissolved during the 1960s, as policymakers realised that these military bases were consuming more security than they could generate. These findings have resonance for British officials charting a return East of Suez today under the banner of 'Global Britain'.